HUBUNGAN KINERJA OTAK DENGAN SPIRITUALITAS MANUSIA DIUKUR DENGAN MENGGUNAKAN INDONESIA SPIRITUAL HEALTH ASSESSMENT PADA DOSEN STAIN MANADO - Dalili, Fitria Angraini; Pasiak, Taufiq F.; Wangko, Sunny (Universitas Sam Ratulangi, 2013)
Abstract: Neuroscience is a science about the nervous system especially the brain. According to Daniel Amen who used SPECT to watch brain activity that was associated with the soul, brain was divided into five main systems: prefrontal cortex, limbic system, ganglia basalis, gyrus cingulatus, and temporal lobe. A person’s spirituality is related to the purpose and meaning of his/her life as a manifestation of one’s relationship with God. Spirituality has four dimensions, namely the meaning of life, positive emotions, spiritual experiences and rituals. In Indonesia, Indonesia Spiritual Health Assessment (ISHA) is used to assess a person’s spirituality. The purpose of this research was to determine the relationship of spirituality with the human brain among Manado STAIN lecturers. This was a descriptive analytic study with 30 respondents. The results were analyzed by using the Spearmen correlation analysis. There was a significant correlation between the performance of the human brain and spirituality, in this case the relationship was between the prefrontal cortex and the meaning of life. Conclusion: There was a strong relationship between the human brain and spirituality. Keywords: brain, ISHA, spirituality. Abstrak: Neurosains adalah ilmu yang mempelajari tentang semua hal yang berkaitan dengan sistem saraf, dalam hal ini otak. Daniel Amen yang menggunakan SPECT dalam mengamati aktivitas otak yang berhubungan dengan jiwa, membagi otak ke dalam lima sistem utama: cortex prefrontalis, sistem limbik, ganglia basalis, gyrus cingulatus, dan lobus temporalis. Spiritualitas seseorang berkaitan dengan tujuan dan makna hidup kehidupan secara keseluruhan, sebagai manifestasi hubungannya dengan Tuhan. Spiritualitas mempunyai empat dimensi yaitu makna hidup, emosi positif, pengalaman spiritual, dan ritual. Di Indonesia, alat ukur spiritual yang digunakan yaitu Indonesia Spiritual Health Assessment (ISHA). Tujuan penelitian ini untuk mengetahui hubungan kinerja otak dengan spiritualitas manusia pada dosen STAIN Manado. Penelitian ini bersifat deskriptif analitik dengan jumlah responden 30 orang. Hasil penelitian dianalisis dengan analisis korelasi Spearmen yang menunjukkan adanya korelasi bermakna antara kinerja otak dan spiritualitas manusia, dalam hal ini hubungan antara cortex prefrontalis dan makna hidup. Simpulan: Terdapat hubungan bermakna antara kinerja otak dan spiritualitas manusia. Kata kunci: otak, ISHA, spiritualitas.